Solving Fuzzy Assignment Problems via Ranking Methods: A Comprehensive Approach - Santosh Kumar,; Sanjay Kumar Suman,; Dilip Kumar Sah,; Manoj Kumar Singh,; Mukesh Kumar Pal,; Raj Kumar,; Nishant Kumar, (International Journal of Scientific Research in Science and Technology, 2025)
This report presents an extensive methodology to solve Fuzzy Assignment Problems (FAP) using ranking methods. Classic Assignment Problems (AP) are generally inadequate in actual applications because they are incapable of dealing with imprecise or fuzzy data. The approach here enlarges the classical model by adding fuzzy concepts, specifically utilizing Triangular Fuzzy Numbers (TFNs), to represent and optimize costs or times in uncertain situations. It provides definitions of the basic features of fuzzy numbers, their arithmetic, a particular ranking function for defuzzification, and formulae for converting different types of fuzzy numbers. An iterative algorithm with nine steps is described as showing a step-by-step method to achieving optimal assignments. Diagrammatic illustrations in even and odd fuzzy number cases describe the applicability of the technique in cost minimization and time saving. The strengths of the methodology, such as its efficiency in computation, simplicity of implementation, and ability to deliver stable solutions in uncertain scenarios, are argued for, placing it as a valuable resource for decision-makers across various operational research applications.
Keywords: Computational Efficiency; Fuzzy Assignment Problems (FAP); Ranking Methods; Defuzzification; Triangular Fuzzy Numbers (TFNs)